1988
DOI: 10.2307/1941261
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochory and Regeneration in A Bald Cypress‐Water Tupelo Swamp Forest

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. The importance of hydrochory, or seed dispersal by water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
186
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(199 citation statements)
references
References 36 publications
(47 reference statements)
11
186
1
1
Order By: Relevance
“…In temperate fioodplain forests, seedling density and survival were greater in elevated microsites (Jones et al 1994). Similarly, seed deposition and germination of temperate bottomland and tropical swamp species was greater in elevated sites such as stumps, logs or mounded soils than in depressions (Schneider and Sharitz 1988;Imbert et al 2000). These observations suggest that debris accumulation, sediment deposition, erosion or any other processes that change elevation, if only by centimeters, may have substantial effects on the plant community.…”
Section: Drought Severity Differential Mortality and Changes In Forementioning
confidence: 82%
See 1 more Smart Citation
“…In temperate fioodplain forests, seedling density and survival were greater in elevated microsites (Jones et al 1994). Similarly, seed deposition and germination of temperate bottomland and tropical swamp species was greater in elevated sites such as stumps, logs or mounded soils than in depressions (Schneider and Sharitz 1988;Imbert et al 2000). These observations suggest that debris accumulation, sediment deposition, erosion or any other processes that change elevation, if only by centimeters, may have substantial effects on the plant community.…”
Section: Drought Severity Differential Mortality and Changes In Forementioning
confidence: 82%
“…Finally, hydrochory, the common mode of seed dispersal for many SFF species, may be advantageous in habitats that experience seasonal flooding as floating seeds are deposited in elevated sites (Schneider and Sharitz 1988;Williamson and Costa 2000). Nevertheless, hydrochory could also reduce establishment success as prolonged flotation might hinder germination and survival through anoxic conditions and depletion of seed reserves (Lopez 2001).…”
Section: Drought Severity Differential Mortality and Changes In Forementioning
confidence: 99%
“…The importance of hydrochory as a vector in wetland habitats was also demonstrated for a forested floodplain in USA by Schneider and Sharitz (1988), who found that 10-100 times as many cypress seeds and tupelo fruits were transported into each plot by water as by wind dispersal alone. Similarly, Jansson and others (2005) showed that along a Swedish river, 36-58% more species colonized flooded plots (subjected to hydrochory) than unflooded plots that were only subjected to anemochory and zoochory.…”
Section: Wind Dispersal Versus Water Dispersalmentioning
confidence: 88%
“…It should be noted that both temporal and permanent seed capture probability parameters were not species-specific in our hydrochorous dispersal model. Seed size or shape might affect deposition probability (see Schneider and Sharitz 1988), and therefore dispersal experiments with different seed types should be performed to improve parameterization. Furthermore, considering the sensitivity of modelled dispersal to permanent capture probability, a reliable way to assess this parameter should be found.…”
Section: Model Performancementioning
confidence: 99%
“…Levine (2003) noted that most patches along a river in California were colonized by propagules from sources within only 100 m upstream. Structurally complex rivers (such as the Vindel River) are efficient at trapping water-dispersed seeds along hydraulically complex reaches and areas with many emergent objects (e.g., cobbles and plant stems; Schneider and Sharitz 1988, Nilsson et al 1991b, Merritt and Wohl 2002, Gurnell et al 2007). Areas of high propagule trapping efficiency have been associated with more species-rich plant communities both in simulations (Merritt and Wohl 2002) and in field experiments (Andersson et al 2000b).…”
Section: Species Similarity To Standing Vegetation Controlsmentioning
confidence: 99%